Investigation of Self-Directed Learning Skills of Distance Education Students - Alanoglu, Muslim; Karabatak, Songul; Karabatak, Murat (Ieee, 2021)
During the pandemic, undergraduate students had to motivate, control, and monitor themselves more than students at other education levels. At this point, the importance of self-directed learning skills that individuals are expected to have has become more evident. For this reason, this research aimed to determine the self-directed learning skill levels of distance undergraduate students and whether these skill levels differ according to the gender variable. For this reason, an easily accessible sampling method was used to reach distance undergraduate students, studying at Firat University in Elazig. The study was conducted with the survey model. Descriptive statistics (kurtosis, skewness values, mean, and standard deviation) were used during the analysis. Independent groups t-test was used to determine whether the students' self-directed learning skills differ according to gender. According to the results, distance undergraduate students always have high self-directed learning skills, and there is no gender effect on students' self-directed learning skills.
9th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 28-29, 2021 -- Firat Univ, Elazig, TURKEY
Keywords: Self-directed learning; distance education; distance undergraduate student